2022
DOI: 10.1002/jcla.24404
|View full text |Cite
|
Sign up to set email alerts
|

The relation of common inflammatory cytokines with anxiety and depression and their values in estimating cardiovascular outcomes in coronary heart disease patients

Abstract: Background Inflammatory cytokines are associated with the occurrence and severity of psychological disorders in cerebro‐cardiovascular disease patients. This study aimed to investigate the correlation of inflammatory cytokines with anxiety and depression in coronary heart disease (CHD) patients and their values for estimating cardiovascular outcomes. Methods Totally, 150 CHD patients and 50 healthy subjects were enrolled. Then, tumor necrosis factor (TNF)‐α, interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Psychological complications are common in cardiac-cerebral vascular disease patients ( 13 , 14 , 19 ). It has been reported that anxiety, depression, and cognitive impairment rates can range from 20.4 to 39.2%, 26.2 to 31.2%, and 18.6 to 43.2%, respectively, among AIS patients ( 15 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Psychological complications are common in cardiac-cerebral vascular disease patients ( 13 , 14 , 19 ). It has been reported that anxiety, depression, and cognitive impairment rates can range from 20.4 to 39.2%, 26.2 to 31.2%, and 18.6 to 43.2%, respectively, among AIS patients ( 15 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines are associated with psychological complications among cardiac-cerebral vascular disease patients. For instance, TNF‐α, IL‐1β, IL‐6, and IL‐17A are elevated in coronary heart disease patients with anxiety and depression in comparison to those without these disorders ( 14 ). Elevated TNF‐α was correlated to the occurrence of anxiety and cognitive impairment in AIS patients ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Evidence supported that patients with depression or anxiety had higher TNF-α, IL-6, or CRP levels, which were positively correlated with the severity of anxiety and depression symptoms. [34][35][36][37] Meanwhile, clinical researches showed that hyperhomocysteinemia or deficiency of vitamin B12 or folate was positively correlated with higher TNF-α, IL-6, or CRP levels in the general population or patients with diabetes, rheumatoid arthritis, and angiographic coronary artery disease. [25][26][27][38][39][40][41] However, no studies investigated the association between vitamin B12, folate, tHcy, TNF-α, IL-6, and CRP levels and symptoms of anxiety and depression in adolescent patients.…”
Section: Introductionmentioning
confidence: 99%